Art Therapy-Based Expression Painting Training to Strengthen the Character of Street Children in Semarang City - Mujiyono, Mujiyono; Haryanto, Eko; Kuntoro, Adi; Nusantoro, Eko (Universitas Negeri Semarang, 2025)
Street children are accustomed to living on the streets, in terminals, and in public places, often experiencing emotional stress. Their personalities become harsh, rough, and less sensitive. The solution offered is art therapy -based expression painting training as a way to channel hidden dreams and psychological burdens. The activity targets 15 street children at the Indonesian Gold Foundation Shelter in Semarang. Implementers include lecturers with visual arts expertise and counselors to ensure a more comprehensive and thorough training and mentoring. The program includes material presentations and creative practice in three face-to-face sessions, each lasting 5–6 hours. The expression painting approach uses a cycle-based art therapy that integrates cognitive, psychomotor, and affective aspects. The creative practice in each cycle uses art therapy stages including warm-up, recalling event, emotional expression and issues, restitution, and termination. The training results showed an increase in street children's creativity in painting. The first cycle was marked by hesitation and stiff expressions, while the second cycle demonstrated courage and diverse expressions through color and form. Participants were able to express their emotions in a painting and were able to appreciate it. This evidence confirms that the participants' creativity, sensitivity, and courage increased. The painting training has been able to reduce the psychological burden of trauma they experienced. The outputs include accredited articles, video highlights, local media news, and copyrights.